Wideband Modeling of DC-DC Buck Converter with GaN Transistors - Piotr Musznicki; Pawel B. Derkacz; Piotr J. Chrzan (Energies, 2021)
The general wideband modeling method of the power converter is presented on the example of DC-DC buck converter with GaN High Electron Mobility Transistors (HEMT). The models of all basic and parasitic components are briefly described. The two methods of Printed Circuit Board (PCB) layout parameter extraction are presented. The results of simulation in Saber@Sketch simulation software and measurements are compared. Next, the model of the converter is reduced to obtain one lumped inductance of the input filter PCB for the analytical prediction of transistor turn-off ringing frequency and overvoltage. The practical use of the model is presented for sizing optimal capacitance of snubber.